Statistical influence of travelling distance on home advantage over 57 years in the men`s German first soccer division - Beckmann, N. (German Journal of Exercise and Sport Research, 2022)
A statistical analysis is presented that investigates the dependence of team cities` geographical distances on the effect of home advantage (HA) for 57 years of the men`s German first soccer division ("Bundesliga"), including 17,376 matches (seasons starting from 1964 to 2020). The data shows that the HA can clearly be evidenced in the past and present (statistical p-value< 0.01) and that it also exists for negligible distances (p< 0.01). The HA and the influence of distance on the HA both significantly decreased gradually over the last decades (p< 0.01). For the first and only time, the HA reversed into an away advantage (AA) for the season 2019/2020 (p< 0.01). The influence of distance on HA has been significant (p< 0.01) in the past (before about 1990) and contributed roughly by about half, compared to a situation without HA or AA. It increases with distance and saturates at around 100km. Such saturation behaviour is in line with results from higher divisions of other countries with similar travelling distances such as Italy, Turkey and England. However, the distance-dependent contribution to HA has been approximately halved and reduced to an insignificant amount today. Furthermore, the temporal HA reduction is significantly larger for large distances compared to short distances (p< 0.01). Reporting and quantifying a reduction (p< 0.01) of the distance-dependent contribution to HA over a time span of 57 years is novel.